(untitled) (Constructionism Conference Proceedings, 2025)
This paper examines the importance of facilitation in youth constructionist learning environments, presenting best practices developed through an educational live-action roleplay (edu-larp) curriculum for middle school-aged youth. Drawing on four pilot deployments, we identify strategies for training facilitators in improvisation, role-play, and technical troubleshooting to ensure alignment with constructionist values. We detail how these practices were scaled and supported through the development of training materials and resources for a camp-in-a-box adaptation. Key findings highlight the need for active engagement in role-play during training, the value of adaptable resources, and the effectiveness of narrative framing in motivating STEM engagement. This work contributes to understanding how facilitation practices can enhance informal learning experiences and provides insights into scaling such practices effectively.